2021
DOI: 10.3390/ijerph182312829
|View full text |Cite
|
Sign up to set email alerts
|

Body Size Measurements and Physical Performance of Youth Female Judo Athletes with Differing Menarcheal Status

Abstract: Purpose: To compare body size measurements and physical performance among female youth judo athletes with differing menarcheal status and to identify indicators of physical performance in post-menarcheal girls. Methods: Nineteen young female judo athletes (age 13.9 ± 2.3 years) were divided into a pre-menarche (n = 7) and a post-menarche (n = 12) group. The athletes were evaluated through neuromuscular tests, including standing long jump (SLJ), medicine ball throw (MBT), and handgrip strength (HGS), and judo-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Interestingly, the mean age of menarche observed in our study (11.9 ± 1.3 years) is comparable to the global average of 12 years old 20 and earlier than previously reported age of menarche in athletes (13 to 14 years) 3,8 . Our findings are similar to that of young female judo athletes with an average menarcheal age of 11.8 ± 1.2 years, 21 suggesting that the lower age of menarche in both studies could be attributed to the general declining trend of menarcheal age observed in many developing and developed countries as a result of improved nutrition and better socioeconomic status 22 . While most athletes attained menarche before the age of 15 years, there were still cases of primary amenorrhea within the sport of gymnastics.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the mean age of menarche observed in our study (11.9 ± 1.3 years) is comparable to the global average of 12 years old 20 and earlier than previously reported age of menarche in athletes (13 to 14 years) 3,8 . Our findings are similar to that of young female judo athletes with an average menarcheal age of 11.8 ± 1.2 years, 21 suggesting that the lower age of menarche in both studies could be attributed to the general declining trend of menarcheal age observed in many developing and developed countries as a result of improved nutrition and better socioeconomic status 22 . While most athletes attained menarche before the age of 15 years, there were still cases of primary amenorrhea within the sport of gymnastics.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Sterkowicz-Przybycień and colleagues (2017) verified from 1411 matches that heavyweight female athletes tended to take a longer time in groundwork fights and pause times, while extra-lightweight female athletes have higher groundwork time compared to the male athletes. Lightweight and heavyweight young judo athletes also display different characteristics regarding physical performance (Torres-Luque et al, 2015) and anthropometric measures, especially body fat percentage (Athayde et al, 2017; Torres-Luque et al, 2015). Despite this, the scores seem not to be influenced by the weight categories, but these aspects need further long-term investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In young judo athletes, maturation status is associated with aerobic capacity and strength (Giudicelli, Luz, Sogut, et al, 2021); however these relationships may be affected by anthropometric variables (Giudicelli et al, 2020). It was reported that the somatic maturity, menarcheal status and anthropometric variables were predictors of judo-specific test performance (Athayde et al, 2021;Detanico et al, 2020). Nonetheless, the maturity status did not discriminate competitive levels in young judo athletes (Detanico et al, 2022).…”
Section: Introductionmentioning
confidence: 99%